2023
DOI: 10.3390/ijms24021503
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Fragmentomics: The Novel Promising Biomarker

Abstract: Cell-free DNA molecules are released into the plasma via apoptotic or necrotic events and active release mechanisms, which carry the genetic and epigenetic information of its origin tissues. However, cfDNA is the mixture of various cell fragments, and the efficient enrichment of cfDNA fragments with diagnostic value remains a great challenge for application in the clinical setting. Evidence from recent years shows that cfDNA fragmentomics’ characteristics differ in normal and diseased individuals without the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…cfDNA shows a complex release pattern attributed to the interconnected cellular process and originating sources. Studies in eight different cancer cell lines and patients' plasma samples have elucidated the characteristics of cfDNA, confirming its release exclusively by cancer cells, with different release patterns [211][212][213][214][215][216]. Screening of the bioenergetics flux parameters showed a correlation between cfDNA release patterns and cellular origin, cancer status, and proliferation phase [217][218][219][220].…”
Section: Theranostic Insights In Tumor-tme-bioenergtics Interfacementioning
confidence: 79%
“…cfDNA shows a complex release pattern attributed to the interconnected cellular process and originating sources. Studies in eight different cancer cell lines and patients' plasma samples have elucidated the characteristics of cfDNA, confirming its release exclusively by cancer cells, with different release patterns [211][212][213][214][215][216]. Screening of the bioenergetics flux parameters showed a correlation between cfDNA release patterns and cellular origin, cancer status, and proliferation phase [217][218][219][220].…”
Section: Theranostic Insights In Tumor-tme-bioenergtics Interfacementioning
confidence: 79%
“…There are several explanations for this phenomenon, e.g., the type of circRNA secretion in the blood. Indeed, plasma circRNAs can arise by passive cell death induced by drugs, hypoxia, inflammation, or endogenous molecular pathways, or they can also be actively secreted into the bloodstream packaged in EVs or TEPs [111]. This implies that the comparison of the circRNA profile of plasma and tissue depends on active/passive molecular secretion and tumor/tissue integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research demonstrated elevated levels of cfDNA in patients with cancer ( Song et al, 2022 ; Wu et al, 2022 ) and inflammation ( Schneck et al, 2017 ), indicating that cfDNA analysis could be a valuable tool for health monitoring ( Hayashi et al, 2019 ). Originating from apoptotic or necrotic events and active release mechanisms in the presence of intracellular circulating nucleases ( Qi et al, 2023 ), cfDNA, with its modal size around 166 base pairs (bp) in plasma, has been linked to nucleosomal structures ( Lo et al, 2021 ). Due to the stability of cfDNA molecules in body fluids ( Polini et al, 2019 ), their wealth of genetic and epigenetic information ( Wu et al, 2019 ; Xiao et al, 2022 ), and the noninvasive or minimally invasive nature of body fluid collection for cfDNA analysis ( Ellervik and Vaught, 2015 ), cfDNA is considered an ideal biomarker for disease prevention, diagnosis, treatment, and prognosis ( Szilagyi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%